2018
DOI: 10.1074/jbc.m117.805424
|View full text |Cite
|
Sign up to set email alerts
|

Differential control of Toll-like receptor 4–induced interleukin-10 induction in macrophages and B cells reveals a role for p90 ribosomal S6 kinases

Abstract: Increasing evidence has linked dysregulated interleukin (IL)-10 production by IL-10+ve B cells to autoimmunity, highlighting the importance of improving the understanding of the regulation of IL-10 production in these cells. In both B cells and myeloid cells, IL-10 can be produced in response to Toll-like receptor (TLR) agonists. In macrophages, previous studies have established that mitogen- and stress-activated protein kinases (MSKs) regulate IL-10 production via the phosphorylation of cAMP response element–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 75 publications
(111 reference statements)
3
16
0
Order By: Relevance
“…These data indicate that in vivo, MSK1 activity (and, possibly H3S10) downstream of TLR4, is a sort of a "safety fuse", limiting LPS-induced inflammation. Similar mechanism of IL-10 secretion upon TLR4 activation has been shown for macrophages and B-cells, albeit different kinases are mediating these anti-inflammatory responses: macrophages utilize MSK1, whereas B-cells depend on RSK2 [136].…”
Section: Iκb Kinase α (Ikkα Chuk) and Inflammatory Pathway-induced Ksupporting
confidence: 52%
“…These data indicate that in vivo, MSK1 activity (and, possibly H3S10) downstream of TLR4, is a sort of a "safety fuse", limiting LPS-induced inflammation. Similar mechanism of IL-10 secretion upon TLR4 activation has been shown for macrophages and B-cells, albeit different kinases are mediating these anti-inflammatory responses: macrophages utilize MSK1, whereas B-cells depend on RSK2 [136].…”
Section: Iκb Kinase α (Ikkα Chuk) and Inflammatory Pathway-induced Ksupporting
confidence: 52%
“…Nevertheless, Hildebrand et al indicated that TLR‐4 mediated STAT3 activation remodels myeloid cells towards an immunosuppressive phenotype 27 . Moreover, in the concept of lymphoid lineage, recent findings suggested that signalling through TLR2 and TLR4 directly down‐regulates T‐cell effector function and promotes IL‐10 production by B cells that proposed to be dependent on the STAT3 activation 21,28 . The present obtained results showed that tropisetron strongly up‐regulates LPS‐stimulated TLR2 and TLR4 gene expression.…”
Section: Discussionsupporting
confidence: 56%
“…ERK1/2 signaling has been implicated in IL-10 expression in multiple cell types (Saraiva & O’Garra, 2010; Iyer & Cheng, 2012; Kubo & Motomura, 2012; Sanin et al., 2015; Garaud et al., 2018; Zhang & Kuchroo, 2019). Of particular interest are data revealing that in both human and mouse B-cells, TLR-mediated ERK1/2 activation is critical to induce IL-10 production, suggesting that the expression of MEK1DD may directly upregulate IL-10 transcription in splenic B-cells (Liu et al., 2014; Sutavani et al., 2018). Taken together, these data suggest that ERK1/2 signaling promotes splenic B-cell activation and the expansion of CD5 + CD1d hi and CD138 + B-cell subsets, and may drive IL-10 expression in one or both of these populations.…”
Section: Discussionmentioning
confidence: 99%